Articulating the Unsymbolized: Vocal Fragility and Affective Voice in Mantagi Ratok Practice - Nurkholis Nurkholis (IJCAS (International Journal of Creative and Arts Studies), 2026)
This study examines vocal fragility as an articulatory mechanism through which affective experience is processed within artistic vocal practice. Using a qualitative phenomenological approach, the research is grounded in a practice-led exploration involving vocal exercises, participant reflections, and process documentation. The study focuses on how affective experiences that are not fully symbolized emerge through the body and are articulated through voice. The findings demonstrate that vocal fragility, manifested through broken voice, unstable breath, and fragmented sound, does not function as a technical limitation, but as a condition of articulation. Three interrelated modes are identified: fragmentation, relationality, and articulation, which describe how affective experience is structured and sustained through vocal practice. These modes indicate that voice operates not merely as an expressive medium, but as a dynamic site where body, affect, and meaning are continuously negotiated. The study proposes Mantagi Ratok as a conceptual and practical model of affective vocal articulation, positioning vocal practice as a process of knowledge production grounded in embodied experience. By reframing vocal instability as an operative mechanism rather than a deviation, this research contributes a new understanding of voice as a site where subjective experience is not simply expressed, but actively articulated and transformed.Mengartikulasikan yang Tak Tersimbolkan: Kerapuhan Vokal dan Suara Afektif dalam Praktik Mantagi Ratok Abstrak Penelitian ini mengkaji kerapuhan suara sebagai mekanisme artikulasi melalui mana pengalaman afektif diproses dalam praktik vokal artistik. Dengan menggunakan pendekatan kualitatif fenomenologis, penelitian ini berangkat dari eksplorasi berbasis praktik yang melibatkan latihan vokal, refleksi partisipan, serta dokumentasi proses. Fokus penelitian terletak pada bagaimana pengalaman afektif yang tidak sepenuhnya tersimbolkan muncul melalui tubuh dan diartikulasikan melalui suara. Temuan menunjukkan bahwa kerapuhan suara yang termanifestasi dalam suara pecah, napas tidak stabil, dan bunyi terfragmentasi, tidak berfungsi sebagai keterbatasan teknis, melainkan sebagai kondisi artikulasi. Tiga modus yang saling berkaitan diidentifikasi, yaitu fragmentasi, relasionalitas, dan artikulasi, yang menjelaskan bagaimana pengalaman afektif dibentuk dan dipertahankan melalui praktik vokal. Modus-modus ini menunjukkan bahwa suara tidak hanya berfungsi sebagai medium ekspresi, tetapi sebagai ruang dinamis tempat tubuh, afek, dan makna terus dinegosiasikan. Penelitian ini mengajukan Mantagi Ratok sebagai model konseptual dan praktis artikulasi vokal afektif, dengan menempatkan praktik vokal sebagai proses produksi pengetahuan yang berakar pada pengalaman embodied. Dengan mereposisi ketidakstabilan vokal sebagai mekanisme operasional alih-alih penyimpangan, penelitian ini memberikan pemahaman baru tentang suara sebagai ruang di mana pengalaman subjektif tidak sekadar diekspresikan, tetapi secara aktif diartikulasikan dan ditransformasikan.